Lithium battery composite negative pole piece, preparation method thereof and lithium battery

By adopting a stacked carbon base layer and functional layer structure in lithium batteries, the shortcomings of the existing lithium battery negative electrode materials in terms of high-speed capability and full capacity utilization are solved, and high energy density, good rate performance and cycle stability are achieved.

CN119943857APending Publication Date: 2025-05-06GUILIN UNIV OF ELECTRONIC TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510034744.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-09
Publication Date
2025-05-06

AI Technical Summary

Technical Problem

The existing lithium battery negative electrode materials have shortcomings in high-speed capability and full capacity utilization, resulting in poor rate performance and serious capacity attenuation of lithium batteries.

Method used

The carbon base layer and functional layer structure are adopted in a laminated manner. The carbon base layer is formed by a coating process, the functional layer is formed by a sputtering process, and some functional layer particles enter the carbon base layer to increase the volumetric energy and inhibit the side reaction between the carbon base material and the electrolyte.

Benefits of technology

It realizes the high energy density, good rate performance and cycle stability of lithium batteries, while reducing the volume expansion rate of the negative electrode material, extending the cycle life and improving safety performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119943857A_ABST
    Figure CN119943857A_ABST
Patent Text Reader

Abstract

The embodiment of the invention discloses a lithium battery composite negative pole piece, a preparation method thereof and a lithium battery. The lithium battery negative pole piece comprises a carbon-based layer and a functional layer which are stacked, the carbon-based layer can be formed by adopting a coating mode, and the functional layer can be formed by adopting a sputtering process. According to the lithium battery composite negative pole piece provided by the invention, the loose and porous carbon-based layer and the functional layer with high energy density can be combined, and part of functional layer particles can enter the carbon-based layer, so that the volumetric specific energy of the carbon-based layer can be increased, and the side reaction between the carbon-based material and an electrolyte can be inhibited; meanwhile, the carbon-based material in close contact with the functional layer can assist in improving the conductivity of the functional layer, buffering the volume expansion of the functional layer and stably exerting the advantage of high energy of the functional layer, so that the lithium battery can be high in lithium conduction rate, structural stability and capacity retention rate, has high specific capacity and cycle reversibility, and is suitable for large-scale popularization and application. The cycle life is prolonged, and the safety performance is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of lithium batteries, and in particular to a lithium battery composite negative electrode plate and a preparation method thereof, and a lithium battery. Background Art

[0002] Lithium batteries have attracted attention from people from all walks of life at home and abroad due to their advantages such as long cycle life, high energy and high power density.

[0003] In the related art, graphite has good conductivity and a layered structure. As the negative electrode material of lithium batteries, it can be used as a + However, the limited capacity of graphite is 372 mAh / g, which makes lithium batteries unable to meet the requirements of high energy density. Summary of the invention

[0004] In view of the deficiencies in the prior art, the present application provides a lithium battery composite negative electrode plate and a preparation method thereof, and a lithium battery, which ensures that the lithium-ion battery has a high energy density while having good rate performance and cycle stability. At the same time, it can also reduce the volume expansion rate of the lithium battery negative electrode material and avoid serious capacity decay of the lithium battery.

[0005] To solve the above problems, in a first aspect, the present application provides a lithium battery composite negative electrode plate, which includes:

[0006] current collector;

[0007] At least one carbon-based layer is disposed on the current collector by a coating process;

[0008] At least one functional layer is disposed on a side of the carbon-based layer close to the current collector by a sputtering process, or is disposed on a side of the carbon-based layer away from the current collector by a sputtering process.

[0009] Furthermore, in the composite negative electrode sheet of a lithium battery provided in the present application, multiple carbon-based layers and multiple functional layers are alternately stacked on a current collector.

[0010] Furthermore, in the lithium battery composite negative electrode sheet provided in the present application, the carbon-based layer includes a negative electrode active material, a binder and a conductive agent; or / and,

[0011] The functional layer is obtained by sputtering the energy density contributing body and the structural material in the form of a target material.

[0012] Furthermore, in the lithium battery composite negative electrode plate provided in the present application, the negative electrode active material includes one or more of artificial graphite, natural graphite, mesophase carbon microspheres, soft carbon and hard carbon; or / and,

[0013] The energy density contributors include one or more of silicon, silicon oxide, germanium, germanium oxide, tin, tin oxide, lead, lead oxide, nickel, nickel oxide, cobalt, cobalt oxide, manganese, manganese oxide, titanium, titanium oxide, lead, lead oxide, molybdenum, molybdenum oxide, vanadium, and vanadium oxide; or / and,

[0014] Structural materials include conductive materials and lithium source electrolytes.

[0015] Furthermore, in the lithium battery composite negative electrode plate provided in the present application, the conductive material includes one or more of aluminum, titanium, manganese, vanadium, iron, cobalt, and chromium; or / and,

[0016] The lithium source electrolyte includes one or more of lithium carbonate, lithium oxide, lithium peroxide, lithium fluoride, lithium nitride, lithium hydroxide, lithium titanate, lithium manganate, lithium phosphorus oxynitride, lithium perchlorate, lithium hexafluorophosphate, and lithium difluorophosphate.

[0017] Furthermore, in the lithium battery composite negative electrode plate provided in the present application, the atmosphere required for the sputtering process includes one or more of argon, nitrogen, ammonia, hydrogen, chlorine, oxygen, fluorine, methane, carbon monoxide, and hydrogen fluoride.

[0018] Furthermore, in the lithium battery composite negative electrode plate provided in the present application, the thickness of the carbon-based layer is 25 to 250 μm; or / and,

[0019] The thickness of the functional layer is 2.5 to 25 μm; or / and,

[0020] The radio frequency sputtering power of the sputtering process is 50-300W, the sputtering deposition time is 60-600min, and the distance between the sputtering target and the current collector is 60-90mm.

[0021] Furthermore, in the lithium battery composite negative electrode plate provided in the present application, the lithium battery composite negative electrode plate is applied to lithium ion batteries, lithium metal batteries, semi-solid lithium batteries or solid-state lithium batteries.

[0022] In a second aspect, the present application also provides a method for preparing a composite negative electrode sheet for a lithium battery, which comprises:

[0023] Providing current collector, slurry, energy density contributing main target and structural material target; wherein the slurry includes negative electrode active material, binder and conductive agent;

[0024] The slurry is coated on the current collector to form a carbon-based layer, and the energy density contributing main target and the structural material target are sputtered and deposited in a preset atmosphere to form a functional layer; the functional layer is arranged on the side of the carbon-based layer close to the current collector, or on the side of the carbon-based layer away from the current collector.

[0025] In the third aspect, the present application also provides a lithium battery, which includes a lithium battery negative electrode plate, an electrolyte and a lithium battery positive electrode plate. The lithium battery negative electrode plate is the lithium battery composite negative electrode plate provided in the first aspect, or is prepared by the preparation method of the lithium battery composite negative electrode plate provided in the second aspect.

[0026] The lithium battery negative electrode plate provided by the present application includes a stacked carbon-based layer and a functional layer, the carbon-based layer can be formed by coating, and the functional layer can be formed by sputtering. The lithium battery composite negative electrode plate provided by the present application can realize the combination of a loose and porous carbon-based layer and a high-energy-density functional layer, and some functional layer particles can enter the carbon-based layer, which can not only increase the volume specific energy of the carbon-based layer, but also inhibit the side reaction of the carbon-based material and the electrolyte. At the same time, the carbon-based material in close contact with the functional layer can help improve the conductivity of the functional layer, buffer the volume expansion of the functional layer, and achieve the stable performance of the high-energy advantage of the functional layer, thereby making the lithium battery have a high lithium conduction rate, high structural stability and high capacity retention rate, and the lithium battery has a high specific capacity and cycle reversibility, which prolongs the cycle life and improves the safety performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 A schematic diagram of the first structure of a composite negative electrode sheet for a lithium battery provided in an embodiment of the present application;

[0028] Figure 2 A second structural schematic diagram of a composite negative electrode sheet for a lithium battery provided in an embodiment of the present application;

[0029] Figure 3 A third structural schematic diagram of a lithium battery composite negative electrode sheet provided in an embodiment of the present application;

[0030] Figure 4 A fourth structural schematic diagram of a lithium battery composite negative electrode sheet provided in an embodiment of the present application;

[0031] Figure 5 A fifth structural schematic diagram of a composite negative electrode sheet for a lithium battery provided in an embodiment of the present application;

[0032] Figure 6 A comparison chart of the cycle performance of lithium batteries made from the negative electrode sheets of lithium batteries of Example 1 of the present application and Comparative Example 1 and Comparative Example 2 at 0.1C (1C = 4200 mA / g);

[0033] Figure 7A comparison chart of the cycle performance of lithium batteries made from the negative electrode sheets of lithium batteries of Example 2 and Comparative Example 1 of the present application at 0.1C (1C = 4200 mA / g);

[0034] Figure 8 This is a comparison chart of the cycle performance of lithium batteries made from the negative electrode sheets of lithium batteries of Example 3 and Comparative Example 1 of the present application at 0.1C (1C = 4200 mA / g);

[0035] Fig. 9 A comparison chart of the cycle performance of lithium batteries made from the negative electrode sheets of lithium batteries of Example 4 of the present application and Comparative Example 3 and Comparative Example 4 at 1C (1C = 994 mA / g);

[0036] Fig.10 A comparison chart of the cycle performance of lithium batteries made from the negative electrode sheets of lithium batteries of Example 5 and Comparative Example 1 of the present application at 0.1C (1C = 4200 mA / g);

[0037] Fig.11 This is a comparison chart of the cycle performance of lithium batteries made from the negative electrode sheets of lithium batteries of Example 6 of the present application and Comparative Example 1 at 0.1C (1C = 4200 mA / g);

[0038] Fig.12 A comparison chart of the cycle performance of lithium batteries made from the negative electrode sheets of lithium batteries of Example 7 of the present application and Comparative Examples 5 and 6 at 0.1C (1C = 2100 mA / g);

[0039] Fig.13 A comparison chart of the cycle performance of lithium batteries made from the negative electrode sheets of lithium batteries of Example 8 and Comparative Example 5 at 0.1C (1C = 2100 mA / g);

[0040] Fig.14 This is a comparison chart of the cycle performance of lithium batteries made from the negative electrode sheets of lithium batteries of Example 9 of the present application and Comparative Example 3 at 1C (1C=994mA / g). DETAILED DESCRIPTION

[0041] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0042] It should also be understood that the terms used in this application specification are only for the purpose of describing specific embodiments and are not intended to limit the application. As used in this application specification and the appended claims, unless the context clearly indicates otherwise, the singular forms "a", "an" and "the" are intended to include plural forms.

[0043] It should be further understood that the term “and / or” used in the specification and appended claims refers to any combination and all possible combinations of one or more of the associated listed items, and includes these combinations.

[0044] In the related technology, alloy-type negative electrode materials such as silicon, tin, lead, and magnesium have high theoretical capacity and can meet the high energy density requirements of lithium batteries. However, due to the conductivity (≈10 -3 S / cm) and Li + Diffusion coefficient (10 -14 ~10 -13 m 2 / S) is poor, and there are also serious problems such as volume expansion (≈300%), resulting in poor high-rate capability and full capacity utilization in lithium batteries.

[0045] In order to solve the technical problems of poor high rate capability and full capacity utilization of alloy-type negative electrode materials in lithium batteries, alloy-type negative electrode materials are usually nano-sized, alloyed, and multi-phase structures are designed to inhibit expansion and increase the cycle stability of negative electrode materials. However, the above methods are not only complex in process, but also the lithium batteries prepared do not have high specific capacity and cycle reversibility.

[0046] To this end, the present application provides a lithium battery composite negative electrode plate and a preparation method thereof, and a lithium battery. The lithium battery negative electrode plate includes a stacked carbon-based layer and a functional layer, the carbon-based layer can be formed by coating, and the functional layer can be formed by a sputtering process. The lithium battery composite negative electrode plate provided by the present application can realize the combination of a loose and porous carbon-based layer and a high-energy-density functional layer, and some functional layer particles can enter the carbon-based layer, which can not only increase the volume specific energy of the carbon-based layer, but also inhibit the side reaction of the carbon-based material with the electrolyte. At the same time, the carbon-based material in close contact with the functional layer can help improve the conductivity of the functional layer, buffer the volume expansion of the functional layer, and achieve the stable performance of the high-energy advantage of the functional layer, thereby making the lithium battery have a high lithium conduction rate, high structural stability and high capacity retention rate, and the lithium battery has a high specific capacity and cycle reversibility, which prolongs the cycle life and improves safety performance.

[0047] See also Figure 1 , Figure 2 , Figure 3 , Figure 4 and Figure 5 , Figure 1 A schematic diagram of the first structure of a composite negative electrode sheet for a lithium battery provided in an embodiment of the present application; Figure 2 A second structural schematic diagram of a composite negative electrode sheet for a lithium battery provided in an embodiment of the present application; Figure 3 A third structural schematic diagram of a lithium battery composite negative electrode sheet provided in an embodiment of the present application; Figure 4 A fourth structural schematic diagram of a lithium battery composite negative electrode sheet provided in an embodiment of the present application; Figure 5 This is a fifth structural schematic diagram of the lithium battery composite negative electrode plate provided in an embodiment of the present application.

[0048] like Figure 1-Figure 5 As shown, the present application provides a lithium battery composite negative electrode plate, which includes:

[0049] current collector;

[0050] At least one carbon-based layer is disposed on the current collector by a coating process;

[0051] At least one functional layer is disposed on a side of the carbon-based layer close to the current collector by a sputtering process, or is disposed on a side of the carbon-based layer away from the current collector by a sputtering process.

[0052] Specifically, the carbon-based layer can be understood as a carbon-based material used in lithium-ion batteries, which plays a role in storing and releasing charge in the battery. Carbon-based materials mainly include hard carbon, soft carbon and graphite, etc., which have the advantages of good conductivity, low cost and mature manufacturing process. The functions of the functional layer can include increasing the lithium insertion speed, improving the cycle performance and energy density of the battery, and preventing the occurrence of lithium precipitation.

[0053] In this embodiment, at least one carbon-based layer and a functional layer are provided on the current collector, and the functional layer can be provided between the current collector and the carbon-based layer, or the functional layer can be provided on the side of the carbon-based layer away from the current collector. At the same time, when multiple carbon-based layers and functional layers are provided on the current collector, the carbon-based layers and the functional layers can be alternately stacked on the current collector. Among them, there can be three carbon-based layers and three functional layers on the current collector, there can also be two carbon-based layers and two functional layers, and there can also be one carbon-based layer and one functional layer.

[0054] It should be noted that the number of carbon-based layers and functional layers on the current collector can be selected according to practical applications, and this application does not make any specific restrictions.

[0055] At the same time, in order to ensure the high lithium conduction rate, structural stability and capacity retention rate of the lithium battery, the slurry corresponding to the carbon-based layer can be coated on the current collector, and then the alloy material can be sputtered on the carbon-based layer by a sputtering process to form a composite negative electrode plate; or the alloy material can be first sputtered on the current collector to form a functional layer, and then the carbon-based layer is coated on the side of the functional layer away from the current collector to form a composite negative electrode plate, thereby solving the problem of high volume expansion rate and low electrical conductivity of materials such as silicon, germanium, tin, lead, nickel, cobalt, manganese, titanium, lead, molybdenum, and vanadium as a single substance or oxide, thereby improving the problems of poor rate performance and severe capacity attenuation of lithium batteries.

[0056] In some embodiments, the carbon-based layer includes a negative electrode active material, a binder, and a conductive agent.

[0057] In this embodiment, the slurry corresponding to the carbon-based layer can be composed of a negative electrode active material, a binder and a conductive agent. When preparing the slurry, the negative electrode active material, the conductive agent and the binder can be dispersed in a solvent at a mass ratio of 80:10:10, stirred evenly to form a slurry, and then the slurry is evenly coated on the surface of the current collector or the functional layer, and then baked and rolled to obtain a lithium battery composite negative electrode sheet.

[0058] Among them, the negative electrode active material includes one or more of artificial graphite, natural graphite, mesophase carbon microbeads, soft carbon and hard carbon; the binder includes one or more of polyvinylidene fluoride, polyacrylic acid, polyacrylonitrile, polytetrafluoroethylene, sodium carboxymethyl cellulose, styrene-butadiene rubber and water-soluble artificial rubber; the conductive agent is one or more of Super-P, SFG-6, KS6, CNTs and VGCF.

[0059] It can be seen that the lithium battery composite negative electrode plate provided in the present application contains less conductive agent and binder, which can reduce the amount of binder and additives used while achieving stable high specific energy under thick coating process, and will have great application potential in the future development of lithium batteries.

[0060] In some embodiments, the functional layer is obtained by sputtering an energy density contributing body and a structural material in the form of a target.

[0061] In this embodiment, the functional layer in the composite negative electrode plate of the lithium battery can be obtained by sputtering the energy density contributing body and the structural material in the form of a target material, which can not only improve the energy density of the lithium battery, but also can be in close contact with the carbon-based layer, so that the lithium conduction rate of the lithium battery is high, the structural stability and the capacity retention rate are high, the lithium battery has a high specific capacity and cycle reversibility, extends the cycle life, and improves the safety performance.

[0062] Among them, when the functional layer is deposited on the carbon-based layer, some functional layer particles can enter the carbon-based layer to increase the volume specific energy of the carbon-based layer and inhibit the side reaction between the carbon-based material and the electrolyte. When the carbon-based layer is coated on the functional layer, the carbon-based material in close contact with the functional layer can help improve the conductivity of the functional layer, buffer the volume expansion of the functional layer, and realize the stable performance of the high energy advantage of the functional layer.

[0063] In some embodiments, the energy density contributing entities include one or more of silicon element, silicon oxide, germanium element, germanium oxide, tin element, tin oxide, lead element, lead oxide, nickel element, nickel oxide, cobalt element, cobalt oxide, manganese element, manganese oxide, titanium element, titanium oxide, lead element, lead oxide, molybdenum element, molybdenum oxide, vanadium element, and vanadium oxide.

[0064] In some embodiments, the structural material includes a conductive material and a lithium source electrolyte. The conductive material includes one or more of aluminum, titanium, manganese, vanadium, iron, cobalt, and chromium. The lithium source electrolyte includes one or more of lithium carbonate, lithium oxide, lithium peroxide, lithium fluoride, lithium nitride, lithium hydroxide, lithium titanate, lithium manganate, lithium phosphorus oxygen nitrogen, lithium perchlorate, lithium hexafluorophosphate, and lithium difluorophosphate.

[0065] In some embodiments, the atmosphere required for the sputtering process includes one or more of argon, nitrogen, ammonia, hydrogen, chlorine, oxygen, fluorine, methane, carbon monoxide, and hydrogen fluoride.

[0066] Furthermore, in some embodiments, the atmosphere required for the sputtering process includes two or more of argon, nitrogen, ammonia, hydrogen, chlorine, oxygen, fluorine, methane, carbon monoxide, and hydrogen fluoride.

[0067] In some embodiments, the thickness of the carbon-based layer is 25 to 250 μm; the thickness of the functional layer is 2.5 to 25 μm; the RF sputtering power of the sputtering process is 50 to 300 W, the sputtering deposition time is 60 to 600 min, and the distance between the sputtering target and the current collector is 60 to 90 mm. Preferably, the distance between the sputtering target and the current collector is 80 mm.

[0068] In addition, it should be noted that during the sputtering process, the current collector is a chemical power source negative electrode current collector, and the temperature of the current collector is controlled to be 25°C to 500°C.

[0069] In some embodiments, the lithium battery composite negative electrode plate is applied to a lithium ion battery, a lithium metal battery, a semi-solid lithium battery or a solid-state lithium battery.

[0070] In some embodiments, the present application also provides a method for preparing a composite negative electrode sheet for a lithium battery, which comprises:

[0071] Providing current collector, slurry, energy density contributing main target and structural material target; wherein the slurry includes negative electrode active material, binder and conductive agent;

[0072] The slurry is coated on the current collector to form a carbon-based layer, and the energy density contributing main target and the structural material target are sputtered and deposited in a preset atmosphere to form a functional layer; the functional layer is arranged on the side of the carbon-based layer close to the current collector, or on the side of the carbon-based layer away from the current collector.

[0073] The lithium battery composite negative electrode plate provided in the present application can combine a loose and porous carbon-based layer with a high-energy-density functional layer. Some functional layer particles can enter the carbon-based layer, which can not only increase the volume specific energy of the carbon-based layer, but also inhibit the side reaction of the carbon-based material with the electrolyte. At the same time, the carbon-based material in close contact with the functional layer can help improve the conductivity of the functional layer, buffer the volume expansion of the functional layer, and achieve stable performance of the high-energy advantage of the functional layer, thereby making the lithium battery have a high lithium conduction rate, high structural stability and high capacity retention rate. The lithium battery has a high specific capacity and cycle reversibility, extends the cycle life, and improves safety performance.

[0074] It should be noted that when multiple carbon-based layers and multiple functional layers are alternately stacked on the current collector, they only need to be alternately performed on the current collector in their respective ways, and this application does not make any specific limitation on this.

[0075] In some embodiments, the present application also provides a lithium battery, which includes a lithium battery negative electrode plate, an electrolyte and a lithium battery positive electrode plate. The lithium battery negative electrode plate is a lithium battery composite negative electrode plate provided in the present application, or is prepared by the preparation method of the lithium battery composite negative electrode plate provided in the present application.

[0076] The negative electrode plate of a lithium battery provided by the present application comprises a carbon-based layer and a functional layer arranged in a stacked manner, wherein the carbon-based layer can be formed by coating, and the functional layer can be formed by a sputtering process. The negative electrode plate of a lithium battery provided by the present application combines a loose and porous carbon-based layer with a functional layer with a high energy density, and some particles of the functional layer can enter the carbon-based layer, which can not only increase the volume specific energy of the carbon-based layer, but also inhibit the side reaction of the carbon-based material with the electrolyte, and at the same time, the carbon-based material in close contact with the functional layer can help improve the conductivity of the functional layer, buffer the volume expansion of the functional layer, and achieve the stable performance of the high energy advantage of the functional layer, thereby making the lithium conduction rate of the lithium battery high, the structural stability and the capacity retention rate high, and the lithium battery has a high specific capacity and cycle reversibility, which prolongs the cycle life and improves the safety performance.

[0077] The beneficial effects of the present application are further illustrated below in conjunction with the embodiments.

[0078] Embodiment 1

[0079] A method for preparing a composite negative electrode sheet for a lithium battery, the specific steps are as follows:

[0080] 1) The natural graphite, conductive agent SP, and PVDF solvent are prepared. First, the natural graphite powder is placed in a crucible, then placed in a muffle furnace, and dry air is introduced. The temperature is raised to 600°C at a heating rate of 3°C / min, sintered for 6 hours, and cooled naturally. The natural graphite and conductive agent SP are mixed and ground, and the obtained powder is mixed with the prepared PVDF binder and NMP solvent in a slurry mixer at a mass ratio of 80:10:10:190. Then the stirred slurry is coated on one side of the copper foil surface, dried at 80°C in an oven for 6 hours, and rolled to form a carbon-based layer A with a thickness of 30 μm.

[0081] 2) The electrode A obtained in step 1) is fixed in a vacuum sputtering chamber, and the side with the active material A layer is used as the sputtering surface; a pure Si target with a purity of 99.999% is selected as the sputtering source, and the distance between it and the sputtering surface is 80 mm. Ar gas ion beam is used to pre-sputter the silicon target for 10 minutes to remove oxides and other impurities on its surface. When the vacuum degree reaches 1.0×10 -4 After the temperature was set to 400 °C, the vacuum chamber atmosphere was adjusted to a mixed atmosphere of high-purity argon and nitrogen in a ratio of 4:1. The substrate was heated to 100 °C and sputtered for 3 h using a 200 W RF power supply to prepare a functional layer B with a thickness of about 3.2 μm to form Figure 1 The lithium battery composite negative electrode sheet with a two-layer structure of a copper foil current collector, a carbon-based layer, and a functional layer is shown;

[0082] 3) The lithium battery composite negative electrode sheet prepared in this embodiment is assembled into a lithium battery. The specific operation is as follows: a button battery CR2016 is used as a mold for evaluating the negative electrode material, and the assembly is carried out in a glove box filled with argon gas with an oxygen content and a water content of less than 0.1ppm. The electrolyte is a mixed solution of 1 mol / L LiPF6 and EC:DEC:DMC in a volume ratio of 1:1:1. Celgard 2320 is used as a diaphragm, and a metal lithium sheet is used as a counter electrode and a reference electrode. The button battery is assembled in the glove box.

[0083] The 2016 button battery prepared as above was subjected to a long cycle test with a test current density of 0.1C and a charge and discharge voltage of 0.01 to 2V.

[0084] Embodiment 2

[0085] A method for preparing a composite negative electrode sheet for a lithium battery, the specific steps are as follows:

[0086] 1) Prepare slurry from natural graphite, conductive agent SP, and PVDF solvent. First, natural graphite powder is placed in a crucible, then placed in a muffle furnace, introduced with dry air, heated to 600°C at a heating rate of 3°C / min, sintered for 6 hours, cooled naturally, mixed and ground natural graphite and conductive agent SP, and the obtained powder was mixed with the prepared PVDF binder and NMP solvent in a slurry mixer at a mass ratio of 80:10:10:190, and then the stirred slurry was coated on one side of the copper foil surface, dried in an oven at 80°C for 6 hours, and rolled to form a carbon-based layer A with a thickness of 30 μm;

[0087] 2) The electrode A obtained in step 1) is fixed in a vacuum sputtering chamber, and the side with the active material A layer is used as the sputtering surface; a pure Si target with a purity of 99.999% is selected as the sputtering source, and the distance between it and the sputtering surface is 80 mm. Ar gas ion beam is used to pre-sputter the silicon target for 10 minutes to remove oxides and other impurities on its surface. When the vacuum degree reaches 1.0×10 -4 After Pa, the vacuum chamber atmosphere was adjusted to a mixed atmosphere of high-purity argon and nitrogen in a ratio of 4:1; the substrate was heated to 100°C and sputtered for 3 hours using a 200W RF power supply to prepare a functional layer B with a thickness of 3.2 μm;

[0088] 3) A third graphite layer is coated on the two-layer electrode sheet obtained in step 2), and the specific steps are consistent with step 1) of this embodiment, and the electrode sheet obtained is the third carbon-based layer A;

[0089] 4) In the three-layer electrode piece obtained in step 3), a fourth functional layer is sputtered. The specific steps are consistent with step 2) of this embodiment. The electrode piece obtained is the fourth functional layer B, so as to form Figure 2 The lithium battery composite negative electrode sheet having a four-layer structure of a copper foil current collector, a carbon-based layer, a functional layer, a carbon-based layer, and a functional layer is shown;

[0090] 5) The lithium battery composite negative electrode sheet prepared in this embodiment is assembled into a lithium battery. The specific operation is as follows: a button battery CR2016 is used as a mold for evaluating the negative electrode material, and the assembly is carried out in a glove box filled with argon gas with an oxygen content and a water content of less than 0.1 ppm. The electrolyte is a mixed solution of 1 mol / L LiPF6 and EC:DEC:DMC in a volume ratio of 1:1:1. Celgard 2320 is used as a diaphragm, and a metal lithium sheet is used as a counter electrode and a reference electrode. The button battery is assembled in the glove box.

[0091] The 2016 button battery prepared as above was subjected to a long cycle test with a test current density of 0.1C and a charge and discharge voltage of 0.01 to 2V.

[0092] Embodiment 3

[0093] A method for preparing a composite negative electrode sheet for a lithium battery, the specific steps are as follows:

[0094] 1) The natural graphite, conductive agent SP, and PVDF solvent are prepared. First, the natural graphite powder is placed in a crucible, and then placed in a muffle furnace, dry air is introduced, and the temperature is increased to 600° C. at a heating rate of 3° C. / min, sintered for 6 hours, and naturally cooled. The natural graphite and the conductive agent SP are mixed and ground, and the obtained powder is mixed with the prepared PVDF binder and NMP solvent in a slurry mixer at a mass ratio of 80:10:10:190; then the stirred slurry is coated on one side of the copper foil surface, dried in an oven at 80° C. for 6 hours, and rolled to form a carbon-based layer A with a thickness of 30 μm;

[0095] 2) The electrode A obtained in step 1) is fixed in a vacuum sputtering chamber, and the side with the active material A layer is used as the sputtering surface; a pure Si target with a purity of 99.999% is selected as the sputtering source, and the distance between it and the sputtering surface is 80 mm. Ar gas ion beam is used to pre-sputter the silicon target for 10 minutes to remove oxides and other impurities on its surface. When the vacuum degree reaches 1.0×10 -4 After Pa, the vacuum chamber atmosphere was adjusted to a mixed atmosphere of high-purity argon and nitrogen in a ratio of 4:1; the substrate was heated to 100°C and sputtered for 3 hours using a 200W RF power supply to prepare a functional layer B with a thickness of 3.2 μm;

[0096] 3) A third graphite layer is coated on the two-layer electrode sheet obtained in step 2), and the specific steps are consistent with step 1) of this embodiment, and the electrode sheet obtained is the third carbon-based layer A;

[0097] 4) sputtering a fourth functional layer on the three-layer electrode piece obtained in step 3), the specific steps are consistent with step 2) of this embodiment, and the electrode piece obtained is the fourth functional layer B;

[0098] 5) Repeat steps 3) and 4) twice to obtain the fifth to eighth layers of electrodes, respectively. Figure 3 The lithium battery composite negative electrode sheet with an eight-layer structure of a copper foil current collector, a carbon-based layer, a functional layer, a carbon-based layer, and a functional layer is shown;

[0099] 6) The lithium battery composite negative electrode sheet prepared in this embodiment is assembled into a lithium battery. The specific operation is as follows: a button battery CR2016 is used as a mold for evaluating the negative electrode material, and the assembly is carried out in a glove box filled with argon gas with an oxygen content and a water content of less than 0.1 ppm. The electrolyte is a mixed solution of 1 mol / L LiPF6 and EC:DEC:DMC in a volume ratio of 1:1:1. Celgard 2320 is used as a diaphragm, and a metal lithium sheet is used as a counter electrode and a reference electrode. The button battery is assembled in the glove box.

[0100] The 2016 button battery prepared as above was subjected to a long cycle test with a test current density of 0.1C and a charge and discharge voltage of 0.01 to 2V.

[0101] Embodiment 4

[0102] A method for preparing a composite negative electrode sheet for a lithium battery, the specific steps are as follows:

[0103] 1) Cut the sputtered copper foil into a size of 60mm*60mm, put it into alcohol and ultrasonicate it for 60s, then ultrasonicate it with deionized water for 60s, and put it in a blast drying oven to dry for 3-5min;

[0104] 2) The copper foil substrate prepared in step 1) was fixed in a vacuum sputtering chamber, and a pure Sn target with a purity of 99.99% was selected as a sputtering source. The distance between the target and the copper foil substrate was 80 mm. When the vacuum degree reached 1.0×10 -4 After Pa, the Sn target was pre-sputtered with Ar gas ion beam for 10 minutes to remove oxides and other impurities on its surface; the power selected for the RF sputtering of the Sn target was 100 W, and the atmosphere of the vacuum chamber was adjusted to a mixed atmosphere of high-purity argon and oxygen in a ratio of 3:1; the substrate was heated to 300°C and the sputtering time was 2h to prepare a composite film with a thickness of 0.9 μm, thereby obtaining the functional layer B.

[0105] 3) The functional layer B obtained in step 2) is used as a substrate, and then a graphite slurry is prepared by a coating process. The slurry is configured by natural graphite, a conductive agent SP, and a PVDF solvent. First, natural graphite powder is placed in a crucible, and then placed in a muffle furnace, dry air is introduced, and the temperature is increased to 600° C. at a heating rate of 3° C. / min, sintered for 6 hours, and naturally cooled. The natural graphite and the conductive agent SP are mixed and ground, and the obtained powder is mixed with the configured PVDF binder and NMP solvent in a mass ratio of 80:10:10:190 in a slurry mixer; then the stirred slurry is coated on one side of the functional layer B, dried in an oven at 80° C. for 6 hours, and rolled to form a carbon-based layer A with a thickness of 30 μm, so as to form Figure 4 The lithium battery composite negative electrode sheet with a two-layer structure of a copper foil current collector, a functional layer and a carbon-based layer is shown;

[0106] 4) The lithium battery composite negative electrode sheet prepared in this embodiment is assembled into a lithium battery. The specific operation is as follows: a button battery CR2016 is used as a mold for evaluating the negative electrode material, and the assembly is carried out in a glove box filled with argon gas with an oxygen content and a water content of less than 0.1ppm. The electrolyte is a mixed solution of 1 mol / L LiPF6 and EC:DEC:DMC in a volume ratio of 1:1:1. Celgard 2320 is used as a diaphragm, and a metal lithium sheet is used as a counter electrode and a reference electrode. The 2016 button battery prepared above is subjected to a long cycle test, and the test current density is 0.1C and the charge and discharge voltage is 0.01~2V.

[0107] Embodiment 5

[0108] A method for preparing a composite negative electrode sheet for a lithium battery, the specific steps are as follows:

[0109] 1) The natural graphite, conductive agent SP, and PVDF solvent are prepared. First, the natural graphite powder is placed in a crucible, then placed in a muffle furnace, and dry air is introduced. The temperature is raised to 600°C at a heating rate of 3°C / min, sintered for 6 hours, and cooled naturally. The natural graphite and conductive agent SP are mixed and ground, and the obtained powder is mixed with the prepared PVDF binder and NMP solvent in a slurry mixer at a mass ratio of 80:10:10:190. Then the stirred slurry is coated on one side of the copper foil surface, dried at 80°C in an oven for 6 hours, and rolled to form a carbon-based layer A with a thickness of 30 μm.

[0110] 2) The electrode A obtained in step 1) is fixed in a vacuum sputtering chamber, and the side with the active material A layer is used as the sputtering surface; a pure Si target is selected as the energy density contributor, and an Al target is used as a structural material, wherein the purity of the target materials is 99.999%, and the distance between the target material and the sputtering surface is 80 mm. When the vacuum degree reaches 1.0×10 -4 After Pa, the target material was pre-sputtered with Ar gas ion beam for 10 minutes to remove oxides and other impurities on its surface; the power selected for RF sputtering was Si:Al = 200W:50W, and the Si target sputtering atmosphere was adjusted to argon, and the Al target sputtering atmosphere was adjusted to a mixed atmosphere of argon and nitrogen in a ratio of 4:1; the substrate was heated to 300°C, the sputtering time was 2h, and the prepared film thickness was 0.9μm, so as to obtain the functional layer B, in order to form Figure 1 The lithium battery composite negative electrode sheet with a two-layer structure of a copper foil current collector, a carbon-based layer, and a functional layer is shown;

[0111] 3) The lithium battery composite negative electrode sheet prepared in this embodiment is assembled into a lithium battery. The specific operation is as follows: a button battery CR2016 is used as a mold for evaluating the negative electrode material, and the assembly is carried out in a glove box filled with argon gas with an oxygen content and a water content of less than 0.1ppm. The electrolyte is a mixed solution of 1 mol / L LiPF6 and EC:DEC:DMC in a volume ratio of 1:1:1. Celgard 2320 is used as a diaphragm, and a metal lithium sheet is used as a counter electrode and a reference electrode. The button battery is assembled in the glove box.

[0112] The 2016 button battery prepared as above was subjected to a long cycle test with a test current density of 0.1C and a charge and discharge voltage of 0.01 to 2V.

[0113] Embodiment 6

[0114] A method for preparing a composite negative electrode sheet for a lithium battery, the specific steps are as follows:

[0115] 1) The natural graphite, conductive agent SP, and PVDF solvent are prepared. First, the natural graphite powder is placed in a crucible, then placed in a muffle furnace, and dry air is introduced. The temperature is raised to 600°C at a heating rate of 3°C / min, sintered for 6 hours, and cooled naturally. The natural graphite and conductive agent SP are mixed and ground, and the obtained powder is mixed with the prepared PVDF binder and NMP solvent in a slurry mixer at a mass ratio of 80:10:10:190. Then the stirred slurry is coated on one side of the copper foil surface, dried at 80°C in an oven for 6 hours, and rolled to form a carbon-based layer A with a thickness of 30 μm.

[0116] 2) The electrode A obtained in step 1) is fixed in a vacuum sputtering chamber, with the side with the active material A layer as the sputtering surface; a pure Si target material is selected as the main energy density contributor, and an Al target material is selected as a structural material, wherein the purity of the target materials is 99.999%, and the distance between the target material and the sputtering surface is 80 mm. When the vacuum degree reaches 1.0×10-4Pa, the target material is pre-sputtered for 10 minutes using an Ar gas ion beam to remove oxides and other impurities on its surface; the power selected for the RF sputtering is Si:Al=200W:50W, and the sputtering atmosphere of the Si target is adjusted to argon, and the sputtering atmosphere of the Al target is adjusted to a mixed atmosphere with a ratio of argon to nitrogen of 4:1; the substrate is heated to 300°C, the sputtering time is 2h, and the prepared film thickness is 0.9μm, thereby obtaining the functional layer B.

[0117] 3) A third graphite layer is coated on the two-layer electrode sheet prepared in step 2). The specific steps are consistent with step 1) of this embodiment. The electrode sheet prepared is the third carbon-based layer A.

[0118] 4) In the three-layer electrode piece obtained in step 3), a fourth functional layer is sputtered. The specific steps are consistent with step 2) of this embodiment. The electrode piece obtained is the fourth functional layer B, so as to form Figure 2 The lithium battery composite negative electrode sheet having a four-layer structure of a copper foil current collector, a carbon-based layer, a functional layer, a carbon-based layer, and a functional layer is shown;

[0119] 5) The lithium battery composite negative electrode sheet prepared in this embodiment is assembled into a lithium battery. The specific operation is as follows: a button battery CR2016 is used as a mold for evaluating the negative electrode material, and the assembly is carried out in a glove box filled with argon gas with an oxygen content and a water content of less than 0.1 ppm. The electrolyte is a mixed solution of 1 mol / L LiPF6 and EC:DEC:DMC in a volume ratio of 1:1:1. Celgard 2320 is used as a diaphragm, and a metal lithium sheet is used as a counter electrode and a reference electrode. The button battery is assembled in the glove box.

[0120] The 2016 button battery prepared as above was subjected to a long cycle test with a test current density of 0.1C and a charge and discharge voltage of 0.01 to 2V.

[0121] Embodiment 7

[0122] A method for preparing a composite negative electrode sheet for a lithium battery, the specific steps are as follows:

[0123] 1) Cut the sputtered copper foil into a size of 60mm*60mm, put it into alcohol and ultrasonicate it for 60s, then ultrasonicate it with deionized water for 60s, and put it in a blast drying oven to dry for 3-5min;

[0124] 2) The copper foil substrate prepared in step 1) is fixed in a vacuum sputtering chamber, SiO2 powder is hammered into a target and placed as a sputtering source in magnetron sputtering. The distance between the SiO2 sputtering source and the copper foil substrate is 80 mm. The SiO2 target is pre-sputtered for 10 minutes using an Ar gas ion beam to remove oxides and other impurities on its surface. When the vacuum degree reaches 1.0×10-4Pa, the vacuum chamber atmosphere is adjusted to a mixed atmosphere of high-purity argon and nitrogen in a ratio of 4:1. The substrate is heated to 100°C and sputtered for 3 hours using a radio frequency power supply with an output of 200 W to prepare a functional layer B with a thickness of 3 μm.

[0125] 3) The functional layer B obtained in step 2) is used as a substrate, and then a graphite slurry is prepared through a coating process. The slurry is prepared from natural graphite, conductive agent SP, and PVDF solvent. First, natural graphite powder is placed in a crucible, and then placed in a muffle furnace, dry air is introduced, and the temperature is raised to 600°C at a heating rate of 3°C / min, sintered for 6 hours, and naturally cooled. The natural graphite and conductive agent SP are mixed and ground, and the obtained powder is mixed with the prepared PVDF binder and NMP solvent in a slurry mixer at a mass ratio of 80:10:10:190. Then the stirred slurry is coated on one side of the functional layer B, dried in an oven at 80°C for 6 hours, and rolled to form a carbon-based layer A with a thickness of 30μm to form Figure 5 The lithium battery composite negative electrode sheet with a four-layer structure of a copper foil current collector, a functional layer, a carbon-based layer, a functional layer, and a carbon-based layer is shown;

[0126] 4) The lithium battery composite negative electrode sheet prepared in this embodiment is assembled into a lithium battery. The specific operation is as follows: a button battery CR2016 is used as a mold for evaluating the negative electrode material, and the assembly is carried out in a glove box filled with argon gas with an oxygen content and a water content of less than 0.1 ppm. The electrolyte is a mixed solution of 1 mol / L LiPF6 and EC:DEC:DMC in a volume ratio of 1:1:1. Celgard 2320 is used as a diaphragm, and a metal lithium sheet is used as a counter electrode and a reference electrode. The button battery is assembled in the glove box.

[0127] The 2016 button battery prepared as above was subjected to a long cycle test with a test current density of 0.1C and a charge and discharge voltage of 0.01 to 2V.

[0128] Embodiment 8

[0129] A method for preparing a composite negative electrode sheet for a lithium battery, the specific steps are as follows:

[0130] 1) Cut the sputtered copper foil into a size of 60mm*60mm, put it into alcohol and ultrasonicate it for 60s, then ultrasonicate it with deionized water for 60s, and put it in a blast drying oven to dry for 3-5min;

[0131] 2) The copper foil substrate prepared in step 1) was fixed in a vacuum sputtering chamber, and the SiO2 powder was hammered into a target and placed as a sputtering source in a magnetron sputtering chamber. The distance between the SiO2 sputtering source and the copper foil substrate was 80 mm. When the vacuum degree reached 1.0×10 -4 After Pa, the SiO2 target was pre-sputtered with Ar gas ion beam for 10 minutes to remove oxides and other impurities on its surface; the power selected for the RF sputtering of the SiO2 target was 200W, and the atmosphere of the vacuum chamber was adjusted to a mixed atmosphere of high-purity argon and nitrogen in a ratio of 4:1; the substrate was heated to 300°C and the sputtering time was 2h to prepare a nitrogen-modified SiO2 film with a thickness of 0.6μm, thus obtaining the functional layer B.

[0132] 3) The functional layer B obtained in step 2) is used as a substrate, and then a graphite slurry is prepared by a coating process. The slurry is configured by natural graphite, conductive agent SP, and PVDF solvent. First, natural graphite powder is placed in a crucible, and then placed in a muffle furnace, dry air is introduced, and the temperature is increased to 600°C at a heating rate of 3°C / min, sintered for 6h, and naturally cooled. The natural graphite and conductive agent SP are mixed and ground, and the obtained powder is mixed with the configured PVDF binder and NMP solvent in a slurry mixer at a mass ratio of 80:10:10:190. Then the stirred slurry is coated on one side of the functional layer B, dried at 80°C in an oven for 6h, and rolled to form a carbon-based layer A with a thickness of 30μm.

[0133] 4) In the three-layer electrode piece prepared in step 3), a third functional layer is sputtered. The specific steps are consistent with step 2) of this embodiment. The electrode piece prepared is the third functional layer B.

[0134] 5) A fourth graphite layer is coated on the three-layer electrode obtained in step 4). The specific steps are the same as step 3) of this embodiment. The electrode obtained is the fourth carbon-based layer A to form Figure 5 The lithium battery composite negative electrode sheet with a four-layer structure of a copper foil current collector, a functional layer, a carbon-based layer, a functional layer, and a carbon-based layer is shown;

[0135] 6) The lithium battery composite negative electrode sheet prepared in this embodiment is assembled into a lithium battery. The specific operation is as follows: a button battery CR2016 is used as a mold for evaluating the negative electrode material, and the assembly is carried out in a glove box filled with argon gas with an oxygen content and a water content of less than 0.1 ppm. The electrolyte is a mixed solution of 1 mol / L LiPF6 and EC:DEC:DMC in a volume ratio of 1:1:1. Celgard 2320 is used as a diaphragm, and a metal lithium sheet is used as a counter electrode and a reference electrode. The button battery is assembled in the glove box.

[0136] The 2016 button battery prepared as above was subjected to a long cycle test with a test current density of 0.1C and a charge and discharge voltage of 0.01 to 2V.

[0137] Embodiment 9

[0138] A method for preparing a composite negative electrode sheet for a lithium battery, the specific steps are as follows:

[0139] 1) Cut the sputtered copper foil into a size of 60mm*60mm, put it into alcohol and ultrasonicate it for 60s, then ultrasonicate it with deionized water for 60s, and put it in a blast drying oven to dry for 3-5min;

[0140] 2) The copper foil substrate prepared in step 1) is fixed in a vacuum sputtering chamber, and a pure Sn target is selected as the main energy density contributor, and a Li2CO3 powder target is selected as the structural material, wherein the purity of the target is 99.99%, and the distance between the target and the sputtering surface is 80 mm. When the vacuum degree reaches 1.0×10 -4 After Pa, the target material was pre-sputtered with an Ar gas ion beam for 10 minutes to remove oxides and other impurities on its surface; the selected power for RF sputtering was Si:Li2CO3=100W:20W, the sputtering atmosphere was argon, the substrate was heated at 300°C, the sputtering time was 2h, and the prepared film thickness was 0.9μm, thus obtaining the functional layer B.

[0141] 3) The functional layer B obtained in step 2) is used as a substrate, and then a graphite slurry is prepared by a coating process. The slurry is configured by natural graphite, conductive agent SP, and PVDF solvent. First, natural graphite powder is placed in a crucible, and then placed in a muffle furnace, dry air is introduced, and the temperature is increased to 600°C at a heating rate of 3°C / min, sintered for 6h, and naturally cooled. The natural graphite and conductive agent SP are mixed and ground, and the obtained powder is mixed with the configured PVDF binder and NMP solvent in a slurry mixer at a mass ratio of 80:10:10:190. Then the stirred slurry is coated on one side of the functional layer B, dried at 80°C in an oven for 6h, and rolled to form a carbon-based layer A with a thickness of 30μm.

[0142] 4) In the three-layer electrode piece prepared in step 3), a third functional layer is sputtered. The specific steps are consistent with step 2) of this embodiment. The electrode piece prepared is the third functional layer B.

[0143] 5) A fourth graphite layer is coated on the three-layer electrode obtained in step 4). The specific steps are the same as step 3) of this embodiment. The electrode obtained is the fourth carbon-based layer A to form Figure 5 The lithium battery composite negative electrode sheet with a four-layer structure of a copper foil current collector, a functional layer, a carbon-based layer, a functional layer, and a carbon-based layer is shown;

[0144] 6) The lithium battery composite negative electrode sheet prepared in this embodiment is assembled into a lithium battery. The specific operation is as follows: a button battery CR2016 is used as a mold for evaluating the negative electrode material, and the assembly is carried out in a glove box filled with argon gas with an oxygen content and a water content of less than 0.1 ppm. The electrolyte is a mixed solution of 1 mol / L LiPF6 and EC:DEC:DMC in a volume ratio of 1:1:1. Celgard 2320 is used as a diaphragm, and a metal lithium sheet is used as a counter electrode and a reference electrode. The button battery is assembled in the glove box.

[0145] The 2016 button battery prepared as above was subjected to a long cycle test with a test current density of 0.1C and a charge and discharge voltage of 0.01 to 2V.

[0146] Comparative Example 1

[0147] A method for preparing a pure silicon negative electrode sheet for a lithium battery, the specific steps are as follows:

[0148] 1) Cut the sputtered copper foil into a size of 60mm*60mm, put it into alcohol and ultrasonicate it for 60s, then ultrasonicate it with deionized water for 60s, and put it in a blast drying oven to dry for 3-5min;

[0149] 2) The copper foil substrate prepared in step 1 was fixed in a vacuum sputtering chamber, and a pure Si target with a purity of 99.999% was selected as a sputtering source. The distance between the target and the copper foil substrate was 80 mm. When the vacuum degree reached 1.0×10 -4 After Pa, the silicon target was pre-sputtered with an Ar gas ion beam for 10 minutes to remove oxides and other impurities on its surface; the power selected for the RF sputtering of the silicon target was 200W, and then the substrate was heated to 300°C in an argon atmosphere for 2 hours to prepare a pure silicon film with a thickness of 0.9μm to form a pure silicon negative electrode;

[0150] 3) The pure silicon negative electrode sheet prepared in Comparative Example 1 was assembled into a lithium battery. The specific operation was as follows: a button battery CR2016 was used as a mold for evaluating the negative electrode material. The assembly was carried out in a glove box filled with argon gas and the oxygen content and water content were both less than 0.1 ppm. The electrolyte was a mixed solution of 1 mol / L LiPF6 and EC:DEC:DMC in a volume ratio of 1:1:1. Celgard 2320 was used as a diaphragm, and a metal lithium sheet was used as a counter electrode and a reference electrode. The button battery was assembled in the glove box.

[0151] The 2016 button battery prepared as above was subjected to a long cycle test with a test current density of 0.1C and a charge and discharge voltage of 0.01 to 2V.

[0152] Comparative Example 2

[0153] A method for preparing a lithium battery silicon nitride-carbon composite negative electrode plate, the specific steps are as follows:

[0154] 1) Cut the sputtered copper foil into a size of 60mm*60mm, put it into alcohol and ultrasonicate it for 60s, then ultrasonicate it with deionized water for 60s, and put it in a blast drying oven to dry for 3-5min;

[0155] 2) The copper foil substrate prepared in step 1 was fixed in a vacuum sputtering chamber, and a pure silicon target with a purity of 99.999% was used as the first sputtering source, and a carbon target with a purity of 99.999% was used as the second sputtering source. The distance between the target and the copper foil substrate was 80 mm. When the vacuum degree reached 1.0×10 -4After Pa, the target material was pre-sputtered with an Ar gas ion beam for 10 minutes to remove oxides and other impurities on its surface; the corresponding atmosphere of the pure silicon target material was adjusted to a mixed atmosphere of high-purity argon and nitrogen in a ratio of 4:1; the corresponding atmosphere of the pure carbon target material was a high-purity argon atmosphere; a co-deposition treatment was performed for 2 hours using a power ratio of Si:C=4:1 (200W:50W), and the substrate temperature was maintained at 300°C during the deposition period to prepare a pure silicon film with a thickness of 0.9μm to form a silicon nitride-carbon composite electrode;

[0156] 3) The silicon nitride-carbon composite electrode prepared in Comparative Example 2 was assembled into a lithium battery. The specific operation was as follows: a button battery CR2016 was used as a mold for evaluating the negative electrode material, and the assembly was carried out in a glove box filled with argon gas with an oxygen content and a water content of less than 0.1 ppm. The electrolyte was a mixed solution of 1 mol / L LiPF6 and EC:DEC:DMC in a volume ratio of 1:1:1. Celgard 2320 was used as a diaphragm, and a metal lithium sheet was used as a counter electrode and a reference electrode, and the battery was assembled into a button battery in the glove box.

[0157] The 2016 button battery prepared as above was subjected to a long cycle test with a test current density of 0.1C and a charge and discharge voltage of 0.01 to 2V.

[0158] Comparative Example 3

[0159] A method for preparing a pure tin negative electrode sheet for a lithium battery, the specific steps are as follows:

[0160] 1) Cut the sputtered copper foil into a size of 60mm*60mm, put it into alcohol and ultrasonicate it for 60s, then ultrasonicate it with deionized water for 60s, and put it in a blast drying oven to dry for 3-5min;

[0161] 2) The copper foil substrate prepared in step 1 was fixed in a vacuum sputtering chamber, and a pure Sn target with a purity of 99.99% was selected as a sputtering source. The distance between the target and the copper foil substrate was 80 mm. When the vacuum degree reached 1.0×10 -4Pa After that, the Sn target was pre-sputtered for 10 minutes using an Ar gas ion beam to remove oxides and other impurities on its surface; the power selected for the Sn target RF sputtering was 100 W, and then the substrate was heated to 300°C under argon conditions for a sputtering time of 2 hours to prepare a pure tin film with a thickness of 0.9 μm to form a pure tin negative electrode;

[0162] 3) The pure tin electrode prepared in Comparative Example 3 was assembled into a lithium battery. The specific operation was as follows: a button battery CR2016 was used as a mold for evaluating the negative electrode material. The assembly was carried out in a glove box filled with argon gas and the oxygen content and water content were both less than 0.1 ppm. The electrolyte was a mixed solution of 1 mol / L LiPF6 and EC:DEC:DMC in a volume ratio of 1:1:1. Celgard 2320 was used as a diaphragm, and a metal lithium sheet was used as a counter electrode and a reference electrode. The button battery was assembled in the glove box.

[0163] The 2016 button battery prepared as above was subjected to a long cycle test with a test current density of 0.1C and a charge and discharge voltage of 0.01 to 2V.

[0164] Comparative Example 4

[0165] A method for preparing a SnO2-C negative electrode sheet for a lithium battery, the specific steps are as follows:

[0166] 1) Place the sputtered copper foil in alcohol and perform ultrasonic treatment for 60 seconds, then perform ultrasonic treatment with deionized water for 60 seconds, and place in a blast drying oven to dry for 3-5 minutes;

[0167] 2) The copper foil substrate prepared in step 1 was fixed in a vacuum sputtering chamber, and a pure tin target with a purity of 99.99% was used as the first sputtering source, and a carbon target with a purity of 99.999% was used as the second sputtering source. The distance between the target and the copper foil substrate was 80 mm. When the vacuum degree reached 1.0×10 -4 After Pa, the target material was pre-sputtered with an Ar gas ion beam for 10 minutes to remove oxides and other impurities on its surface; the corresponding atmosphere of the pure tin target material was adjusted to a mixed atmosphere of high-purity argon and oxygen in a ratio of 3:1; the corresponding atmosphere of the pure carbon target material was a high-purity argon atmosphere; a co-deposition treatment was performed for 2 hours using a power ratio of Sn:C=4:1 (100W:25W), and the substrate temperature was maintained at 300°C during the deposition period to prepare a pure silicon film with a thickness of 0.9μm to form a SnO2-C negative electrode;

[0168] 3) The SnO2-C negative electrode sheet prepared in Comparative Example 4 was assembled into a lithium battery. The specific operation was as follows: a button battery CR2016 was used as a mold for evaluating the negative electrode material. The assembly was carried out in a glove box filled with argon gas and having an oxygen content and a water content of less than 0.1 ppm. The electrolyte was a mixed solution of 1 mol / L LiPF6 and EC:DEC:DMC in a volume ratio of 1:1:1. Celgard 2320 was used as a diaphragm, and a metal lithium sheet was used as a counter electrode and a reference electrode. The battery was assembled into a button battery in the glove box.

[0169] The 2016 button battery prepared as above was subjected to a long cycle test with a test current density of 0.1C and a charge and discharge voltage of 0.01 to 2V.

[0170] Comparative Example 5

[0171] A method for preparing a lithium battery SiO2 negative electrode sheet, the specific steps are as follows:

[0172] 1) Place the sputtered copper foil in alcohol and perform ultrasonic treatment for 60 seconds, then perform ultrasonic treatment with deionized water for 60 seconds, and place in a blast drying oven to dry for 3-5 minutes;

[0173] 2) The copper foil substrate prepared in step 1 was fixed in a vacuum sputtering chamber, and the SiO2 powder was hammered into a target and placed as a sputtering source in the magnetron sputtering. The distance between the SiO2 sputtering source and the copper foil substrate was 80 mm. When the vacuum degree reached 1.0×10 -4 After Pa, the silicon target was pre-sputtered with an Ar gas ion beam for 10 minutes to remove oxides and other impurities on its surface; the power selected for the RF sputtering of the silicon target was 200W, and then the substrate was heated to 300°C in an argon atmosphere for 2 hours to prepare a SiO2 film with a thickness of 0.6μm to form a SiO2 negative electrode;

[0174] 3) The SiO2 negative electrode sheet prepared in Comparative Example 5 was assembled into a lithium battery. The specific operation was as follows: a button battery CR2016 was used as a mold for evaluating the negative electrode material. The assembly was carried out in a glove box filled with argon gas and the oxygen content and water content were both less than 0.1 ppm. The electrolyte was a mixed solution of 1 mol / L LiPF6 and EC:DEC:DMC in a volume ratio of 1:1:1. Celgard 2320 was used as a diaphragm, and a metal lithium sheet was used as a counter electrode and a reference electrode. The battery was assembled into a button battery in the glove box.

[0175] The 2016 button battery prepared as above was subjected to a long cycle test with a test current density of 0.1C and a charge and discharge voltage of 0.01 to 2V.

[0176] Comparative Example 6

[0177] A method for preparing a lithium battery silicon nitride-carbon composite negative electrode plate, the specific steps are as follows:

[0178] 1) Cut the sputtered copper foil into a size of 60mm*60mm, put it into alcohol and ultrasonicate it for 60s, then ultrasonicate it with deionized water for 60s, and put it in a blast drying oven to dry for 3-5min;

[0179] 2) The copper foil substrate prepared in step 1 is fixed in a vacuum sputtering chamber, and a pure silicon target with a purity of 99.999% is used as the first sputtering source, and a carbon target with a purity of 99.999% is used as the second sputtering source, and the distance between the target and the copper foil substrate is 80 mm. When the vacuum degree reaches 1.0×10-4Pa, the target is pre-sputtered for 10 minutes using an Ar gas ion beam to remove oxides and other impurities on its surface; the corresponding atmosphere of the pure silicon target is adjusted to a mixed atmosphere of high-purity argon and nitrogen in a ratio of 4:1; the corresponding atmosphere of the pure carbon target is a high-purity argon atmosphere; a power ratio of Si:C=4:1 (200W:50W) is used for co-deposition for 2 hours, and the substrate temperature is maintained at 300°C during the deposition period to prepare a pure silicon film with a thickness of 0.9μm to form a silicon nitride-carbon composite negative electrode;

[0180] 3) The silicon nitride-carbon composite negative electrode sheet prepared in Comparative Example 6 was assembled into a lithium battery. The specific operation was as follows: a button battery CR2016 was used as a mold for evaluating the negative electrode material. The assembly was carried out in a glove box filled with argon gas and the oxygen content and water content were both less than 0.1 ppm. The electrolyte was a mixed solution of 1 mol / L LiPF6 and EC:DEC:DMC in a volume ratio of 1:1:1. Celgard 2320 was used as a diaphragm, and a metal lithium sheet was used as a counter electrode and a reference electrode. The button battery was assembled in the glove box.

[0181] The 2016 button battery prepared as above was subjected to a long cycle test with a test current density of 0.1C and a charge and discharge voltage of 0.01 to 2V.

[0182] The relevant electrochemical test results of each lithium battery are as follows:

[0183] The lithium battery provided in Example 1 has an initial discharge capacity of 1999.91 mAh / g at a current density of 420 mA / g, a discharge capacity of 1862.34 mAh / g after 800 cycles, and a capacity retention rate of 93%.

[0184] The lithium battery provided in Example 2 has an initial discharge capacity of 2301.5 mAh / g at a current density of 420 mA / g. After 800 cycles, the discharge capacity is 2106.47 mAh / g, and the capacity retention rate is 91%.

[0185] The lithium battery provided in Example 3 has an initial discharge specific capacity of 2854.4 mAh / g at a current density of 420 mA / g, a reversible specific capacity of 2650.21 mAh / g after 800 cycles, and a capacity retention rate of 92.8%.

[0186] The lithium battery provided in Example 4 has an initial discharge specific capacity of 1193.8 mAh / g at a current density of 994 mA / g, a reversible specific capacity of 830.3 mAh / g after 800 cycles, and a capacity retention rate of 70%.

[0187] The lithium battery provided in Example 5 has an initial discharge capacity of 1602.07 mAh / g at a current density of 420 mA / g. After 1000 cycles, the discharge capacity is 1387.97 mAh / g, and the capacity retention rate is 86.6%.

[0188] The lithium battery provided in Example 6 has an initial discharge capacity of 1880.06 mAh / g at a current density of 420 mA / g. After 1000 cycles, the discharge capacity is 1513.69 mAh / g, and the capacity retention rate is 80.5%.

[0189] The lithium battery provided in Example 7 has an initial discharge capacity of 1097.31 mAh / g at a current density of 210 mA / g. After 1000 cycles, the discharge capacity is 987.04 mAh / g, and the capacity retention rate is 90%.

[0190] The lithium battery provided in Example 8 has an initial discharge capacity of 1742.4 mAh / g at a current density of 210 mA / g. After 1000 cycles, the discharge capacity is 1310 mAh / g, and the capacity retention rate is 75%.

[0191] The lithium battery provided in Example 9 has an initial discharge capacity of 997.8 mAh / g at a current density of 994 mA / g. After 800 cycles, the discharge capacity is 690 mAh / g, and the capacity retention rate is 69.2%.

[0192] The lithium battery provided in Comparative Example 1 has an initial discharge specific capacity of 3226.06 mAh / g at a current density of 420 mA / g, a reversible specific capacity of 233.12 mAh / g after 800 cycles, and a capacity retention rate of 7%.

[0193] The lithium battery provided in Comparative Example 2 has an initial discharge specific capacity of 1888.6 mAh / g at a current density of 420 mA / g, and the capacity decays significantly. After 460 cycles, the capacity retention rate is 38%.

[0194] The lithium battery provided in Comparative Example 3 has an initial discharge capacity of 879.6 mAh / g at a current density of 994 mA / g, a significant capacity decay after 60 cycles, and a discharge capacity close to 0 after 400 cycles.

[0195] The lithium battery provided in Comparative Example 4 has an initial discharge specific capacity of 2130 mAh / g at a current density of 994 mA / g, a reversible specific capacity of 205.4 mAh / g after 800 cycles, and a capacity retention rate of 9.6%.

[0196] The lithium battery provided in Comparative Example 5 has an initial discharge specific capacity of 2071.5 mAh / g at a current density of 210 mA / g, and the capacity decays significantly. After 460 cycles, the capacity remains only 8.79 mAh / g.

[0197] The lithium battery provided in Comparative Example 6 has an initial discharge specific capacity of 1487.4 mAh / g at a current density of 210 mA / g, and the capacity decays significantly. After 460 cycles, the capacity retention rate is 46%.

[0198] It can be seen from the above test results that after the lithium battery composite negative electrode sheet provided in the present application is formed by a coating process and a sputtering process, the lithium battery has a high specific capacity and cycle reversibility, and the cycle life of the lithium battery is greatly improved.

[0199] The above are only specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any technician familiar with the technical field can easily think of various equivalent modifications or replacements within the technical scope disclosed in the present application, and these modifications or replacements should be included in the protection scope of the present application. Therefore, the protection scope of the present application shall be based on the protection scope of the claims.

Claims

1. A lithium battery composite negative electrode plate, characterized in that: include: current collector; At least one carbon-based layer is disposed on the current collector by a coating process; At least one functional layer is disposed on a side of the carbon-based layer close to the current collector by a sputtering process, or is disposed on a side of the carbon-based layer away from the current collector by a sputtering process.

2. The lithium battery composite negative electrode plate according to claim 1, characterized in that: A plurality of carbon-based layers and a plurality of functional layers are alternately stacked on the current collector.

3. The lithium battery composite negative electrode plate according to claim 1, characterized in that: The carbon-based layer comprises a negative electrode active material, a binder and a conductive agent; or / and, The functional layer is obtained by sputtering an energy density contributing body and a structural material in the form of a target material.

4. The lithium battery composite negative electrode plate according to claim 3, characterized in that: The negative electrode active material comprises one or more of artificial graphite, natural graphite, mesophase carbon microbeads, soft carbon and hard carbon; or / and, The energy density contributing entities include one or more of silicon, silicon oxide, germanium, germanium oxide, tin, tin oxide, lead, lead oxide, nickel, nickel oxide, cobalt, cobalt oxide, manganese, manganese oxide, titanium, titanium oxide, lead, lead oxide, molybdenum, molybdenum oxide, vanadium, and vanadium oxide; or / and, The structural material includes a conductive material and a lithium source electrolyte.

5. The lithium battery composite negative electrode plate according to claim 4, characterized in that: The conductive material includes one or more of aluminum, titanium, manganese, vanadium, iron, cobalt, and chromium; or / and, The lithium source electrolyte includes one or more of lithium carbonate, lithium oxide, lithium peroxide, lithium fluoride, lithium nitride, lithium hydroxide, lithium titanate, lithium manganate, lithium phosphorus oxynitride, lithium perchlorate, lithium hexafluorophosphate, and lithium difluorophosphate.

6. The lithium battery composite negative electrode sheet according to any one of claims 1 to 5, characterized in that: The atmosphere required for the sputtering process includes one or more of argon, nitrogen, ammonia, hydrogen, chlorine, oxygen, fluorine, methane, carbon monoxide, and hydrogen fluoride.

7. The lithium battery composite negative electrode sheet according to any one of claims 1 to 5, characterized in that: The thickness of the carbon-based layer is 25 to 250 μm; or / and, The thickness of the functional layer is 2.5 to 25 μm; or / and, The radio frequency sputtering power of the sputtering process is 50-300W, the sputtering deposition time is 60-600min, and the distance between the sputtering target and the current collector is 60-90mm.

8. The lithium battery composite negative electrode sheet according to any one of claims 1 to 5, characterized in that: The lithium battery composite negative electrode plate is applied to lithium ion batteries, lithium metal batteries, semi-solid lithium batteries or solid lithium batteries.

9. A method for preparing a composite negative electrode sheet for a lithium battery, characterized in that: include: Providing a current collector, a slurry, an energy density contributing main target material and a structural material target material; wherein the slurry includes a negative electrode active material, a binder and a conductive agent; The slurry is coated on the current collector to form a carbon-based layer, and the energy density contributing main target and the structural material target are sputtered and deposited in a preset atmosphere to form a functional layer; the functional layer is arranged on a side of the carbon-based layer close to the current collector, or on a side of the carbon-based layer away from the current collector.

10. A lithium battery, characterized in that: It comprises a lithium battery negative electrode sheet, an electrolyte and a lithium battery positive electrode sheet, characterized in that the lithium battery negative electrode sheet is a lithium battery composite negative electrode sheet as described in any one of claims 1 to 8, or is prepared by the preparation method of the lithium battery composite negative electrode sheet as described in claim 9.